The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep28287
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cell epitope specificity determines follicular versus non-follicular helper differentiation in the polyclonal response to influenza infection or vaccination

Abstract: Follicular helper T cells (Tfh) are essential for B cell production of high-affinity, class-switched antibodies. Much interest in Tfh development focuses on the priming environment of CD4 T cells. Here we explored the role that peptide specificity plays in the partitioning of the polyclonal CD4 T cell repertoire between Tfh and NonTfh lineages during the response to influenza. Surprisingly, we found that CD4 T cells specific for different epitopes exhibited distinct tendencies to segregate into Tfh or NonTfh. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…While these processes are critical in early Tfh differentiation, nascent Tfh cells require functional B cell interactions to complete Tfh commitment 37,38 . Finally, the T cell receptor (TCR) of the naïve cell may also shape the differentiation process, given that properties of TCR binding and signaling have been demonstrated to drive Tfh differentiation 3944 .…”
Section: Viral Infections and The T Cell Responsementioning
confidence: 99%
“…While these processes are critical in early Tfh differentiation, nascent Tfh cells require functional B cell interactions to complete Tfh commitment 37,38 . Finally, the T cell receptor (TCR) of the naïve cell may also shape the differentiation process, given that properties of TCR binding and signaling have been demonstrated to drive Tfh differentiation 3944 .…”
Section: Viral Infections and The T Cell Responsementioning
confidence: 99%
“…Second, is Tfh cell avidity important? A recent study of the influenza‐virus‐specific CD4 + T‐cell response indicated that T cells responding to different epitopes exhibited distinct tendencies to develop into Tfh cells, with those exhibiting a higher functional avidity being more likely to become Tfh cells203; but whether Tfh cells of higher avidity also mediate superior help for B cells is not clear. No associations have been reported between HLA class II type and bnAb induction during HIV‐1 infection that may support a role for T‐cell responses of particular specificity favoring or disfavoring bnAb induction47; but as many CD4 T‐cell epitopes are promiscuously presented by multiple HLA class II alleles,204 this does not preclude a relationship between epitope recognition and help for bnAb induction.…”
Section: T Follicular Helper Cells and Their Role In Bnab Inductionmentioning
confidence: 99%
“…Second, is Tfh cell avidity important? A recent study of the influenza-virus-specific CD4 + T-cell response indicated that T cells responding to different epitopes exhibited distinct tendencies to develop into Tfh cells, with those exhibiting a higher functional avidity being more likely to become Tfh cells 203 ; but whether Tfh cells of higher avidity also mediate superior help for B cells is not clear.…”
Section: First Does the Epitope Specificity Of Tfh Cells Impact On Bmentioning
confidence: 99%
“…Although high‐affinity CD4 + T‐cell clones and T‐cell receptors (TCR) with the strongest peptide–MHCII binding show skewed differentiation into Tfh cells, this is most likely due to increased clonal expansion in response to high‐affinity antigens . It has been suggested that although antigen affinity does not correlate with partitioning to Tfh cell fate, different peptide epitopes may dictate T helper type 1 (Th1) versus Tfh cell differentiation . Intriguingly, single cell transfer demonstrated that individual polyclonal T cells specific for a single peptide tend to produce progeny with a specific balance of Th1 and Tfh cells .…”
Section: The Role Of Antigen Presentation In Tfh Cell Differentiationmentioning
confidence: 99%
“…8,9 It has been suggested that although antigen affinity does not correlate with partitioning to Tfh cell fate, different peptide epitopes may dictate T helper type 1 (Th1) versus Tfh cell differentiation. 10 Intriguingly, single cell transfer demonstrated that individual polyclonal T cells specific for a single peptide tend to produce progeny with a specific balance of Th1 and Tfh cells. 11 This divergence was due to enhanced Tfh differentiation with increased aggregate dwell time (the half-life for which a TCR productively binds to its cognate pMHCII ligand).…”
Section: Strength and Duration Of T-cell Receptor Signalmentioning
confidence: 99%